Neuropsychiatric Symptoms and Their Association With Sex, Age, and Enzyme Replacement Therapy in Fabry Disease: A Systematic Review - Mroczek, Magdalena; Maniscalco, Ignazio; Sendel, Manon; Baron, Ralf; Seifritz, Erich; Nowak, Albina (Frontiers in Psychiatry, 2022)
Patients suffering from Fabry disease (FD) have an increased risk of developing neuropsychiatric symptoms (NPS), mostly impairment in cognitive performance and depression. Single cases of psychosis have been reported, however, their association with FD can be coincidental. Furthermore, deficits in social functioning and adaptation as well as specific coping styles in FD patients were observed. Recent studies focused on a longitudinal course of the disease and identified risk factors associated with specific NPS. Since 2001, enzyme replacement therapy (ERT) has been available and in preliminary studies seems to improve cognitive impairment and adaptive skills. In this systematic review we analyze the available literature on the NPS in FD to delineate the spectrum and character of neuropsychiatric manifestations. Further, we investigate if there are any differences in their distribution between males and females, children/adolescents and adults, and individuals treated with ERT and untreated. We discuss the role of the psychological, environmental, and molecular alterations and their correlation to psychiatric manifestations in FD. Finally, we would like to increase awareness of the spectrum of NPS in FD.